The Influence of Leverage, Liquidity and Company Size on Company Value in Hotel, Restaurant and Tourism Sub-Sector Companies Listed on the Indonesian Stock Exchange for the 2020-2022 Period - Karmila, Ika; Prayitno, Yogo Heru (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This research aims to find out how leverage, liquidity and company size influence company value in Hotel, Restaurant and Tourism Subsector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The factors tested in this research are leverage, liquidity, and company size as independent variables, while company value is the dependent variable. The research method used in this research is descriptive and verification methods. The population in this research is Hotel, Restaurant and Tourism Subsector companies listed on the Indonesia Stock Exchange for the 2020-2022 period, totaling 42 companies. The sampling technique used in this research is non-probability sampling with a purposive sampling method, so that the sample in this research is 30 companies. The data analysis used in this research is panel data regression analysis using Eviews 13 software. The research results show that leverage, liquidity and company size influence company value. Apart from that, the research results also show that the influence of leverage, liquidity and company size in contributing to company value is 55.8%.